Cowboy heat wave - Redford, Kim (Redford, Kim. Smokin' hot cowboys., 2022)
"Audrey Oakes has come to Wildcat Bluff County desperate for a break. If she can locate the legendary Hallelujah Ranch bootlegger gold, she can afford the medical treatment that could save her grandmother's life. But the clues in the old family journal lead her straight into a gang of rustlers stealing a herd of mustangs ... Cowboy firefighter Cole Murphy hadn't planned on catching a damsel in distress--he'd been trying to catch the rustlers before they stole the last of his herd. When the wild-eyed beauty on the run asks for his help, he can't say no. but can he trust that Audrey is as innocent as she claims, or will the red-hot connection between them go up in flames?"--